2007
DOI: 10.1002/uog.4045
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of persistent left superior vena cava diagnosed in fetal life

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
6
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 38 publications
5
75
6
6
Order By: Relevance
“…It is also important to emphasize that the spectrum of CHD reported postnatally to be associated with PLSVC correlates well with that observed in most prenatal series, all showing an excess of conotruncal anomalies, septal defects and left heart obstructive disease. However, in contrast with our own results, in which heterotaxy syndromes were overrepresented in fetuses with PLSVC, the almost complete absence of these defects in the postnatal series presented by Postema et al 1 is remarkable and may reflect the high mortality associated with these conditions. …”
Section: Replycontrasting
confidence: 99%
See 1 more Smart Citation
“…It is also important to emphasize that the spectrum of CHD reported postnatally to be associated with PLSVC correlates well with that observed in most prenatal series, all showing an excess of conotruncal anomalies, septal defects and left heart obstructive disease. However, in contrast with our own results, in which heterotaxy syndromes were overrepresented in fetuses with PLSVC, the almost complete absence of these defects in the postnatal series presented by Postema et al 1 is remarkable and may reflect the high mortality associated with these conditions. …”
Section: Replycontrasting
confidence: 99%
“…Therefore, its recognition should prompt a detailed cardiac and extracardiac survey, both prenatally and postnatally. Nevertheless, it is important to keep in mind that the conclusions presented in the three series mentioned by Postema et al were drawn from high-risk populations (up to 40% of CHD in the series of Postema et al 1 ) and, therefore, the real value of the detection of this venous anomaly in an unselected population is still unknown. It is also important to emphasize that the spectrum of CHD reported postnatally to be associated with PLSVC correlates well with that observed in most prenatal series, all showing an excess of conotruncal anomalies, septal defects and left heart obstructive disease.…”
Section: Replymentioning
confidence: 98%
“…Galindo et al [10] found a frequency of 0.2% in fetuses with normal heart and 9% in fetuses with cardiac abnormalities. Nsah et al [11] found an incidence of 9% on 1208 autopsied specimens of fetuses with cardiac abnormalities.…”
Section: Discussionmentioning
confidence: 96%
“…Otherwise, there is a significant morbidity and mortality, which results especially from the associated abnormalities [10,12,13,17]. Identification in the fetal life of the PLSVC increases the risk of cardiac malformation by 50 times [16].…”
Section: Discussionmentioning
confidence: 99%
“…, 32 Others contend that persistent LSVC itself should not constitute an indication for fetal karyotype, as the cardiac defects themselves are the true conditions associated with chromosomal disorders and not the persistent left SVC 4 . Table 1 summarises all the associations with this finding.…”
Section: Discussionmentioning
confidence: 99%